(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The present study aims at analysing the effects of TPR- story telling method on kids at an early preoperational stage. According to Piaget, this stage (age 2-7) is when children‟s language makes rapid progress. Story telling as a pedagogical tool in EFL/ESL has been successfully tried, applied and tested in several classrooms around the globe. The urge to listen to stories is an inborn trait of human beings. It is always a source of inspiration and attracts people despite their age, gender and ethnicity. Stories supply context to hold the listeners attention. This study is based on an attempt by the author of this article, applying TPRS with children at the age of 4 and 3 respectively. The result of the study showed the effectiveness of storytelling in enhancing fluency, vocabulary usages and use of basic grammar, especially tense among children.